Teacherâ Guideline in Designing English Materials in Curriculum 2013 - Edy, Sarwo; Rimadanti, Uci Sherly (ENGLISH FRANCA : Academic Journal of English Language and Education, 2018)
The objectives of this research were knowing the guidelines used by the teachers and describing how the teachers implemented the guidelines in designing English materials in curriculum 2013. The researcher chose descriptive study as the kind of research and presented the results in qualitative way. There were five teachers from some Senior High Schools who had participated as the subjects of the research. The researcher used document analysis and interview to collect the data. Document analysis was used to know what the guidelines used by the teachers in designing English materials were. Then, interview was used to collect the detailed qualitative data expressed in the respondentsâ own words in order to describe the implementation of guidelines by the teachers in designing English materials. The results of this research, based on Howard and Majorâs theory, showed that the teachers used thirteen guidelines and did not use three guidelines in designing English materials. Next, the teachers implemented the guidelines by using syllabus as a guidance, and the materials were designed based on studentsâ experiences, realities and ages. Based on the results of this research, the researcher suggested the teachers to pay more attention to the guidelines provided, because it is important to make the materials which you designed suitable with the standards in syllabus and studentsâ needs.